PENERAPAN ASSESMEN PROYEK UNTUK MENINGKATKAN REPRESENTASI DAN MENGGURANGI KECEMASAN SISWA - Rasilah Rasilah (Universitas Wiralodra, 2019)
The purpose of this study is to see which is better between students who get project assessment learning and students who get conventional learning and the correlation between mathematical anxiety and representation ability. This research method is the Concurrent Embedded Model type Mix Method research, which is a method that combines the use of quantitative and qualitative research methods simultaneously / together (or vice versa) but the bobods vary. The population in this study is all junior high school students of Nu darul Maarif Indramayu took two Class VII samples were randomly assigned. The instruments used were test and non-test instruments. Test instruments in the form of mathematical identification ability tests, questionnaires to determine student attitudes, observations and interviews to find out errors in student answers. Based on the results of data analysis and hypothesis testing, the conclusion is that: 1) there are differences in the increase in the ability of mathematical representation to obtain project assessment learning and students who obtain conventional learning. 2) there is an increase in the ability to get project assessment learning and students who get conventional learning are seen from the initial ability of mathematics (high, medium, low). 3) there is a relationship between the ability of representation with mathematical anxiety, students who use the project assessment learning model experience moderate levels of anxiety, and conventional learning experiences severe levels of anxiety.